Duration of humoral immunity from smallpox vaccination and its cross-reaction with Mpox virus - Entao Li; Xiaoping Guo; Dongxiang Hong; Qizan Gong; Wenyu Xie; Tingting Li; Jian Wang; Xia Chuai; Sandra Chiu (Signal Transduction and Targeted Therapy, 2023)
Abstract The ongoing pandemic caused by mpox virus (MPXV) has become an international public health emergency that poses a significant threat to global health. The vaccinia virus Tiantan strain (VTT) was used to vaccinate against smallpox in China 42 years ago. It is urgent to assess the level of immunity to smallpox in individuals vaccinated 43 or more years ago and evaluate their immunological susceptibility to MPXV. Here, we recruited 294 volunteers and detected the level of residual humoral immunity, including the vaccinia-specific IgG level and neutralizing antibody titer, and the cross-antibodies of MPXV A29L, B6R, A35R, and M1R. Our results showed that the humoral immunity from the smallpox vaccine in the population still remains, and VTT-specific NAb levels wane with age. The majority of the population pre-1981 who should be immunized with VTT still maintains certain levels of MPXV-specific antibodies, in particular, targeting A35R and B6R antigens. Furthermore, we separately analyzed the correlations between the OD450 values of VTT-specific IgG and A35R-specific IgG, B6R-specific IgG, and A29L-specific IgG with plasma samples diluted 1:40, showing a linear correlation (p < 0.0001). Our findings suggest that most Chinese populations still maintain VTT-specific IgG antibodies for 42 or more years after smallpox vaccination and could provide some level of protection against MPXV.